If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 3) + -1x = 31 Reorder the terms: (3 + 5x) + -1x = 31 Remove parenthesis around (3 + 5x) 3 + 5x + -1x = 31 Combine like terms: 5x + -1x = 4x 3 + 4x = 31 Solving 3 + 4x = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4x = 31 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 31 + -3 4x = 31 + -3 Combine like terms: 31 + -3 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| -15+3(p-2)=5(2p-3)+8 | | -6x+4(2x-5)=-25-9x | | x/3+15=25 | | (ln)y=9t+2 | | 6x+4x=15 | | 25q+18=100-13q+70 | | 2(2v-3)=2v-5 | | logy=9t+12 | | (x+4)/2=7 | | 2-x=-10 | | 2x^2-5x+55=0 | | lny=9t+12 | | 1/4(2x-14)=4 | | 3(X-4)=20 | | 7-m=5+3 | | 1.5x+1=4 | | 7a+3=8-2a | | 0=4x^2-8x+15 | | (3x+6z)3= | | 6x-10=4x+6 | | 49p^3q-25pq^3=0 | | x+3+5x= | | 2y^2+48y+288=0 | | 15-5t=0 | | 5(x-2)+4(3x+x)=83 | | 9x^2+24x+20=0 | | 3y+11=17 | | 5(2-x)+4(3x+x)=83 | | 4p+6=2(p+5) | | r+s+rs+s+rs+s= | | 9(0.5x+2)=3(2.25x+27) | | .4w=5 |